Trial shows antipsychotics to be ineffective for treating delirium. (2nd February 2019) - Palmer, Sarah
Abstract : Confusion is common in older people, but an acute confused state or altered perception of reality can indicate delirium. There is presently no medication available to treat this condition, but there are other ways to manage it.